The technology improvement and development of the new design-engineering principles of pilot bore directional drilling; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Shadrina A. V. Anastasiya Viktorovna (Latest Technologies in Oil and Gas Driling, 2016)
Title screen